Structural and Electrical Behavior of (0.70)BiFe1−xCoxO3–(0.30)PbTiO3 Solid Solutions Prepared by Simple Sol-Gel Route. (23rd September 2021) - Sharma, Subhash; Kumar, Pawan; Singh, Vikash; Dwivedi, R. K.; Siqueiros, J. M.; Herrera, O. Raymond
Abstract : Several compositions of the (0.70)BiFe1−x Cox O3 – (0.30)PbTiO3 system for x = 0.00, 0.03, 0.06, 0.09, 0.12 dubbed (0.70)BFCO − (0.30)PT were prepared by sol-gel route. Raman analysis confirmed the coexistence of two phases (rhombohedral and tetragonal) up to x = 0.06 and almost a single tetragonal phase for 0.09 and 0.12 revealed by X-ray diffraction analysis. The effect of Co substitution in BFO-PT in the electrical properties has been discussed. The dielectric permittivity and dielectric loss were improved by the Co substitution in the BFO-PT ceramic. A broad hump was observed for x = 0.0 around the Nèel temperature, disappearing for higher x compositions and it is followed by a low-temperature hump for x = 0.09 and 0.12. A systematic and detailed study on the ac conductivity determines the nature of the conduction mechanisms based on the activation energy values in different temperature regions. These results show that an Arrhenius type of thermally activated process occurs in the low-temperature regime, a small polaron hopping in the intermediate regime and an oxygen vacancy-based mechanism takes place in the high-temperature side. Fourier transform infrared spectra show a strong band corresponding to the Fe–O stretching and O–Fe–O bending vibrations.